2019
DOI: 10.1101/779538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic epidemiology of a complex, multi-species plasmid-borne blaKPC carbapenemase outbreak in Enterobacterales in the UK, 2009-2014

Abstract: Carbapenem resistance in Enterobacterales is a public health threat. Klebsiella pneumoniae carbapenemase (encoded by alleles of the blaKPC family) is one of the commonest transmissible carbapenem resistance mechanisms worldwide. The dissemination of blaKPC has historically been associated with distinct K. pneumoniae lineages (clonal group 258 [CG258]), a particular plasmid family (pKpQIL), and a composite transposon (Tn4401). In the UK, blaKPC has caused a large-scale, persistent outbreak focused on hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A visual comparison of pKpQIL-like plasmids from our collection, together with two published pKpQIL-like plasmids from North-West England (Stoesser et al 2020) and pKpQIL (Leavitt et al 2010), showed the high structural conservation overall ( Figure 4 ). However, two plasmids (from ARGID_31921 and ARGID_24826) had lower nucleotide similarity with pKpQIL over one half, likely as a result of recombination.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…A visual comparison of pKpQIL-like plasmids from our collection, together with two published pKpQIL-like plasmids from North-West England (Stoesser et al 2020) and pKpQIL (Leavitt et al 2010), showed the high structural conservation overall ( Figure 4 ). However, two plasmids (from ARGID_31921 and ARGID_24826) had lower nucleotide similarity with pKpQIL over one half, likely as a result of recombination.…”
Section: Resultsmentioning
confidence: 85%
“…The plasmids include the original pKpQIL sequence (accession GU595196) (Leavitt et al 2010), seven from the PHW collection and two previously sequenced plasmids recovered in North-West England hospitals (Stoesser et al 2020). Open reading frames (ORFs) are depicted as arrows with resistance genes (including bla KPC ) labelled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has stated that OXA-48 containing plasmids from outbreak-related patients could not be distinguished from similar plasmids of non-outbreak related patients based on SNP differences ( 31 ). Interestingly, other studies found bla KPC -containing plasmids to be highly variable in their nucleotide sequence within the same outbreak and even within patients ( 15,20 ). This suggests that the plasmid content could also be highly unstable in vivo during hospital outbreaks.…”
Section: Discussionmentioning
confidence: 95%
“…A pangenome was constructed, and phylogenetic distance based on gene-presence/-absence between the different plasmids was determined using Roary v1.13.2 ( 27 ). All plasmids were pairwise aligned using dnadiff , and a similarity index was calculated between the different plasmids as described by Stoesser et al ( 20 ) (Stoesser-similarity index). This similarity index can vary from 0 (completely unsimilar plasmids) to 1 (identical plasmids) and, contrary to both Roary phylogenetic distance and number of SNP differences, penalises size differences between plasmids.…”
Section: Methodsmentioning
confidence: 99%